Novel ROADM modelling with WSS and OBS to Improve Routing Performance in Optical Network - Kavitha G.R; Indumathi T.S (Institute of Advanced Engineering and Science, 2016)
The area of optical network is on constant point of focus among the research communities owing to potential advantage of long distance communication as well as the routing issues associated with it. Majority of the implemented techniques calls for using expensive hardware or adopting narrowed technical assumptions, for which reason the routing performance couldn’t be optimized to a large extent. The present manuscript proposes a novel technique called as Optimized Routing for Peak Traffic under the scenario of uncertainties in the existing traffic scenario. The proposed solution presents some potential principle that is incorporated in the ROADM design for enhancing the capabilities of the proposed system. The system is evaluated under multiple scenarios of analysis using blocking probabilities, OSNR, bit error rate, iteration etc. The outcome of the proposed system is compared with the one of the existing significant study to benchmark it.